THE EFFECT OF WORK INVOLVEMENT, JOB SATISFACTION, AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. AJS INDORAYA NUSANTARA IN BALIKPAPAN. - Ovigeria Subroto Sinaga; Nurhidayah Syafiah (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The topic of this research is Human Resources. This study aims to determine the effect of job engagement (X1), job satisfaction (X2), and work motivation (X3) on employee performance (Y) at PT. AJS Indoraya Nusantara in Balikpapan. Data were collected using a questionnaire administered to all 34 employees. The analysis tool used was multiple linear regression with the help of SPSS software.All questions were found to be valid and reliable. A multiple regression analysis was then conducted, and the results showed that X1, X2, and X3 had a significant effect, both partially and simultaneously. From the resulting regression equation, Y = 5.528 + 0.475 X1 + 0.278 X2 + 0.225 X3, it can be seen that the independent variable, work engagement (X1), is the most influential variable on employee performance (Y) compared to job satisfaction (X2) and work motivation (X3).